In memoriam: Leonardo Amoroso (Livorno 1952 - Pisa 2021), Università degli Studi di Pisa - Sevilla Fernández, José Manuel (Cuadernos sobre Vico, 2022)
Cuadernos sobre Vico expresses its pain and makes public its sorrow for the death in 2021 of Leonardo Amoroso, a scholar of Vico and linked to Cuadernos sobre Vico, a magazine he supported and on whose pages he collaborated, contributing to the quality of the publication and to the historicization of “Vico in Spanish”.